A neutralizing single-domain antibody that targets the trimer interface of the human metapneumovirus fusion protein - Marlies Ballegeer; Revina C. van Scherpenzeel; Teresa Delgado; Maria Iglesias-Caballero; Blanca García Barreno; Shubham Pandey; Scott A. Rush; Joost A. Kolkman; Vicente Mas; Jason S. McLellan; Xavier Saelens (mBio, 2024)
ABSTRACTHuman metapneumovirus (hMPV) is a leading cause of viral lower respiratory tract disease in children and adults. The hMPV fusion protein F is a trimeric class I fusion protein that is initially synthesized as a precursor (F0) and requires proteolytic activation by a host cell protease to generate the metastable, fusion-competent prefusion conformation of F. hMPV F is considered the main target of the neutralizing antibody response against hMPV infection. We isolated single-domain antibodies (sdAbs) directed against hMPV F that potently neutralize hMPV A and B strains. One of these sdAbs, sdHMPV16, specifically bound to cleaved and uncleaved prefusion F. Co-crystal structure analysis revealed that sdHMPV16 binds to a site located at the trimer interface of prefusion F. Moreover, prophylactic treatment with a sdHMPV16-Fc fusion protein reduced viral titers in the lungs of hMPV-infected cotton rats. In summary, sdHMPV16 broadly neutralizes hMPV, can be turned into a candidate biologic that restricts hMPV replication in an in vivo model, and, unexpectedly, binds to an unconventional epitope at the prefusion F trimer interface.IMPORTANCEHuman metapneumovirus (hMPV) is an important respiratory pathogen for which no licensed antivirals or vaccines exist. Single-domain antibodies represent promising antiviral biologics that can be easily produced and formatted. We describe the isolation and detailed characterization of two hMPV-neutralizing single-domain antibodies that are directed against the fusion protein F. One of these single-domain antibodies broadly neutralizes hMPV A and B strains, can prevent proteolytic maturation of F, and binds to an epitope in the F trimer interface. This suggests that hMPV pre-F undergoes trimer opening or “breathing” on infectious virions, exposing a vulnerable site for neutralizing antibodies. Finally, we show that this single-domain antibody, fused to a human IgG1 Fc, can protect cotton rats against hMPV replication, an important finding for potential future clinical applications.